Influencia de las técnicas grafo plásticas en la adquisición del código alfabético en niños y niñas de 5 años de la unidad educativa fiscal Abdón Calderón del cantón Durán - Mindiola Vera, Carmen Matilde (2016)
The application of the graph-plastic techniques allows the infant to make up and create, this way he or she will express all the cognitive and emotional information, being able to improve his motricity and affectibility, at the same time it strengthens the process as a means in didactics to understand all the topics from different study areas.The present work of research has been elaborated with the purpose of assessing this discipline, in order that the five-year-old children of the "Unidad Educativa Fiscal Abdón Calderón" can improve their motor maturity to start learning the alphabetic code properly. The pedagogy indicates that in order to achieve a correct process of education and learning in the basic elementary, the child should have acquired the basic knowledge of the initial education, allowing the students to reach a correct fine motricity progress. In this way it will be able to succeed the following academic challenges and to achieve his goals. The fine motricity development of the children allows them to be aware of their opportunities and conditions, at the same time, if this process is developed in an organized way, they will show effectively everything that has been done through their learning………